The priorities and emergency treatments of multisystem injuries associated with maxillofacial traumas - Hasan, Ahmed O. (Journal of Baghdad College of Dentistry, 2019)
Background: The purpose of this study is to evaluate the care of multiple trauma victims with maxillofacial injuries in terms of epidemiological distributions, types of injuries, the related different modalities of surgical treatments delivered, and their complications. Materials and Methods: This prospective study was performed on 50 patients with multiple traumas including maxillofacial injuries, caused by different etiological factors, who were brought first to the surgical emergencies department of the Medical City then referred to the Maxillofacial unit in the Specialized Surgeries Hospital, Baghdad, Iraq, during the period from April 2007 to April 2008. Information was documented prospectively from the time of the emergency call to discharge (or death). Results: the age range was from 6 to 63 years, with the most frequent age group for injury being ranged between 21-30 years. The male to female ratio was 6:1. The missile injuries accounted for 90% of multiple traumas with maxillofacial injuries, while civilian injuries accounted for 10% of the cases. The mechanisms of injury, concerning war injuries, were gunshot injuries 46% and blast injuries 44%, while concerning civilian injuries: road traffic accidents 8% and stabbing injuries 2%. Among 50 people injured, 3 (6%) died. Conclusion: The priority during initial treatment is the achievement of patent airway, hemostasis, and the maintenance of vital tissues oxygenation.